A STUDY OF THE EFFECTS OF 15N ION BEAM ON ORGANIC COMPOUNDS - Pilakouta, M.; Aslanoglou, X.; Savidou, A.; Paradellis, T.; Sideris, E. (HNPS Advances in Nuclear Physics, 2020)
Organic compounds EDTA. EDTA-Na and biological samples Bovine Liver and DNA, were irradiated with 15N ions at the energy of 8.5 MeV and the hydrogen lost during bombarding was monitored via the H(15N,aγ)12C resonance reaction. The hydrogen loss curves were fited using a multiple exponential function which indicates different mechanisms with which hydrogen is lost.